2023
DOI: 10.3389/fimmu.2023.1167639
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 3 key genes as novel diagnostic and therapeutic targets for OA and COVID-19

Abstract: BackgroundCorona Virus Disease 2019 (COVID-19) and Osteoarthritis (OA) are diseases that seriously affect the physical and mental health and life quality of patients, particularly elderly patients. However, the association between COVID-19 and osteoarthritis at the genetic level has not been investigated. This study is intended to analyze the pathogenesis shared by OA and COVID-19 and to identify drugs that could be used to treat SARS-CoV-2-infected OA patients.MethodsThe four datasets of OA and COVID-19 (GSE1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Ciclopirox regulates the growth and autophagic cell death of GC cells by regulating the phosphorylation of STAT3 at Tyr705 and Ser727 residues, and suggests that ciclopirox may be a potential treatment for GC [75]. Consistent with this study, Zhang et al identified ciclopirox as a potential therapeutic agent for the treatment of patients with SARS-CoV-2 infection through drug prediction and simulated docking patterns [76]. Resveratrol is considered an anti-inflammatory and antiviral agent.…”
Section: Discussionsupporting
confidence: 69%
“…Ciclopirox regulates the growth and autophagic cell death of GC cells by regulating the phosphorylation of STAT3 at Tyr705 and Ser727 residues, and suggests that ciclopirox may be a potential treatment for GC [75]. Consistent with this study, Zhang et al identified ciclopirox as a potential therapeutic agent for the treatment of patients with SARS-CoV-2 infection through drug prediction and simulated docking patterns [76]. Resveratrol is considered an anti-inflammatory and antiviral agent.…”
Section: Discussionsupporting
confidence: 69%
“…The antifungal drug ciclopirox ethanolamine has been reported to be superior to gemcitabine in a pancreatic cancer model. [ 82 ] In line with this research, Zhang et al [ 83 ] identified ciclopirox as a potential therapeutic agent for treating patients with SARS-CoV-2 infection using drug prediction and simulated docking patterns. Dasatinib can enhance the inhibitory activity of paclitaxel and gemcitabine on human pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 83%
“…Since the emergence of the COVID-19 pandemic in 2019, global confirmed cases have exceeded 700 million, leading to intricate complications that strain patient diagnosis and treatment 38 . The typical clinical symptoms of this disease include fever, dry cough, and fatigue, along with chills, headaches, sore throats, shortness of breath, and difficulty breathing 39 .…”
Section: Discussionmentioning
confidence: 99%